Ultrasound applied to nursing in the Emergency Medical Service (EMS): a scoping review - Enrico Lucenti; Lucrezia Lavelli; Walter De Luca; Maurizio Beretta (Firenze University Press, 2022)
Abstract Background: In recent years, ultrasound has represented a new field of application for nursing. Point of Care UltraSound (POCUS) has been defined as an essential skill in the pre-hospital setting. The primary objective of this scoping review is to describe what are the main ultrasound techniques applied by nurses in the pre-hospital emergency setting. The secondary objective is to identify the different training courses implemented in the various studies selected to learn the necessary ultrasound skills. Methods: We conducted a scoping review. The following databases were consulted: PubMed, Cochrane Library, CINAHL and Google Scholar. For the extraction of useful articles, after identifying the inclusion and exclusion criteria, the PRISMA methodology was used, two authors independently analyzed the identified records, in the event of a conflict a third author intervened. Results: The identified records were initially 815. After the duplicates removal, and screening made by the researcher for inclusion criteria, 6 articles were retrieved for qualitative analysis. The most discussed topic is the recognition of pneumothorax: two studies analyzed a specific educational program on ultrasound for flight nurses, three articles evaluated the us of US to verify the correct insertion of devices, and two explored the skills of nurses in performing ultrasound scans. The first study stated that nurses had 86.4% accuracy, 66.6% sensitivity and 100% specificity in ultrasound using; in the second one, nurses had a sensitivity and specificity of 100% in non-traumatized patients and a sensitivity of 60% and a specificity of 93% in trauma patients. Conclusions: Despite the methodological differences of the selected records, the main ultrasound techniques implemented by nurses in the Emergency Medical Service (EMS) are Focused Assessment with Sonography for Trauma (FAST), Extendend Focused Assessment with Sonography for Trauma (E-FAST), evaluation of pneumothorax and visualization of correct insertion of devices (Endotracheal Tube, Nasogastric Tube). At the level of training in the ultrasound field, on the other hand, a certain heterogeneity is highlighted in the structuring of training courses, both in terms of hours of theory and of controlled practice.